‫تأثير‬‫ممارسة‬ ‫المقارنة‬ ‫المرجعية‬ ‫في‬ ‫تحقيق‬ ‫الأداء‬ ‫المتميز‬ ‫للمؤسسة‬ ‫الإقتصادية‬ ‫دراسة‬‫حالة‬ ‫–‬ ‫مؤسسة‬ ‫مطاحن‬ ‫بلغيث‬ ‫الكبرى‬ ‫بمداوروش‬ ‫س‪/‬ه‬ ‫‪-‬‬ - ‬‫عفاف‫ بكاكرة ‬; كوثر ‫غضابنية‬‫‬ (My University, 2018)
‫‪to‬‬‫‪company‬‬ ‫‪Mills‬‬ ‫‪Belghith‬‬ ‫‪the‬‬ ‫‪at‬‬ ‫‪workers‬‬ ‫‪the‬‬ ‫‪of‬‬ ‫‪attitudes‬‬ ‫‪the‬‬ ‫‪identify‬‬ ‫‪to‬‬ ‫‪was‬‬ ‫‪study‬‬ ‫‪this‬‬ ‫‪of‬‬ ‫‪aim‬‬ ‫‪The‬‬ ‫‪institution.‬‬‫‪the‬‬ ‫‪in‬‬ ‫‪it‬‬ ‫‪of‬‬ ‫‪effect‬‬ ‫‪and‬‬ ‫‪roll‬‬ ‫‪performance,‬‬ ‫‪outstanding‬‬ ‫‪and‬‬ ‫‪benchmarking‬‬ ‫‪of‬‬ ‫‪practice‬‬ ‫‪the‬‬ ‫‪forms,‬‬‫)‪(30‬‬ ‫‪was‬‬ ‫‪wich‬‬ ‫‪method,‬‬ ‫‪sampling‬‬ ‫‪random‬‬ ‫‪simple‬‬ ‫‪the‬‬ ‫‪used‬‬ ‫‪we‬‬ ‫‪month,‬‬ ‫‪April‬‬ ‫‪in‬‬ ‫‪was‬‬ ‫‪study‬‬ ‫‪The‬‬ ‫‪data.‬‬‫‪the‬‬ ‫‪analyze‬‬ ‫‪to‬‬ ‫‪method‬‬ ‫‪analytical‬‬ ‫‪descriptive‬‬ ‫‪the‬‬ ‫‪used‬‬ ‫‪we‬‬ ‫‪of‬‬‫‪practice‬‬ ‫‪the‬‬ ‫‪of‬‬‫‪level‬‬ ‫‪the‬‬ ‫‪is‬‬ ‫‪wich‬‬ ‫‪of‬‬ ‫‪important‬‬ ‫‪most‬‬ ‫‪,the‬‬ ‫‪results‬‬ ‫‪several‬‬ ‫‪has‬‬ ‫‪study‬‬ ‫‪This‬‬ ‫‪significant‬‬‫‪a‬‬ ‫‪of‬‬ ‫‪existence‬‬ ‫‪the‬‬ ‫‪to‬‬ ‫‪addition‬‬ ‫‪,in‬‬ ‫‪high‬‬ ‫‪is‬‬ ‫‪performance‬‬ ‫‪outstanding‬‬ ‫‪and‬‬ ‫‪benchmarking‬‬ ‫‪in‬‬‫‪performance‬‬ ‫‪the‬‬ ‫‪in‬‬ ‫‪stages‬‬ ‫‪benchmarking‬‬ ‫‪the‬‬ ‫‪between‬‬ ‫‪correlation‬‬ ‫‪of‬‬ ‫‪relationship‬‬ ‫‪the‬‬ ‫‪and‬‬ ‫‪effect‬‬ ‫‪the‬‬‫‪of‬‬ ‫‪direction‬‬ ‫‪the‬‬ ‫‪in‬‬ ‫‪signifcance‬‬ ‫‪statistical‬‬ ‫‪of‬‬ ‫‪differances‬‬ ‫‪of‬‬ ‫‪existence‬‬ ‫‪to‬‬ ‫‪addition‬‬ ‫‪in‬‬ ‫‪,‬‬ ‫‪institution‬‬ ‫‪the‬‬ ‫‪the‬‬‫‪encourage‬‬ ‫‪:‬‬ ‫‪to‬‬ ‫‪is‬‬ ‫‪wich‬‬ ‫‪of‬‬ ‫‪important‬‬ ‫‪the‬‬ ‫‪recommendations,‬‬ ‫‪several‬‬ ‫‪reached‬‬ ‫‪study‬‬ ‫‪The‬‬ ‫‪respondent.‬‬ ‫‪been‬‬‫‪have‬‬ ‫‪that‬‬ ‫‪tasks‬‬ ‫‪the‬‬ ‫‪accomplishing‬‬ ‫‪in‬‬ ‫‪skills‬‬ ‫‪their‬‬ ‫‪employing‬‬ ‫‪by‬‬ ‫‪stages‬‬ ‫‪benchmarking‬‬ ‫‪with‬‬ ‫‪work‬‬ ‫‪and‬‬‫‪benchmarking‬‬ ‫‪applying‬‬ ‫‪when‬‬ ‫‪employees‬‬ ‫‪motivating‬‬ ‫‪and‬‬ ‫‪encouraging‬‬ ‫‪performance,‬‬ ‫‪acheived,‬‬ ‫‪application.‬‬‫‪of‬‬ ‫‪ease‬‬ ‫‪ensure‬‬ ‫‪to‬‬ ‫‪system‬‬ ‫‪incentive‬‬ ‫‪effective‬‬ ‫‪an‬‬ ‫‪adopting‬‬ ....................................................... ‬‬